Self-efficacy–kinesiophobia correlation in postoperative patients with primary liver cancer: the chain-mediating effect of postoperative fatigue and negative emotions - Liu, Zhijun; Luo, Xingjuan; Yang, Hui; Ma, Mengqi; He, Hong; Xiao, Hong (Frontiers in Psychology, 2025)
IntroductionEarly postoperative mobilization poses a momentous challenge for patients with primary liver cancer (PLC) after undergoing laparoscopic surgery, and the onset of kinesiophobia can adversely affect their physical activity, mental health, and overall quality of life. This study aims to investigate the impact of self-efficacy on kinesiophobia in postoperative patients with PLC, along with the chain-mediating effect of postoperative fatigue (POF) and negative emotions on self-efficacy and kinesiophobia.MethodsThis cross-sectional study used demographic questionnaires, the Tampa Scale for Kinesiophobia-11 (TSK-11), and the General Self-Efficacy Scale (GSES) to survey 328 patients who underwent laparoscopic surgery for PLC between January and June 2024.ResultsThere was a moderate negative correlation between self-efficacy and kinesiophobia in postoperative patients with PLC (r = −0.544, p < 0.01). POF mediated the self-efficacy–kinesiophobia correlation (= −0.159, 95% confidence interval (CI): [−0.248, −0.052]), accounting for 27.32% of the total effect. Moreover, negative emotions mediated the self-efficacy–kinesiophobia correlation (= −0.108, 95% CI: [−0.281, −0.026]), accounting for 18.56% of the total effect. Furthermore, the chain-mediating effect of POF and negative emotions on self-efficacy and kinesiophobia was significant (= −0.069, 95% CI: [−0.190, −0.019]), with the total indirect effect accounting for 57.56% of the total effect.ConclusionThe prevalence of kinesiophobia is comparatively higher among patients after PLC surgery. Self-efficacy not only directly affects kinesiophobia but also indirectly influences it through POF and negative emotions. This study offers a scientific basis for creating effective interventions to alleviate the adverse physiological and psychological effects of kinesiophobia in postoperative patients with PLC.